Wątek śmierci we współczesnych interpretacjach - Demichev, Andrei (Humanistyka i Przyrodoznawstwo, 2018)
Contemporary understanding od death is a part of our common picture of the world. Death is structurally assimilated with that is never death ex definition. All the masks of death can be easily reduced to only two: discoursiveness or metaphoricalness (if taken in the wider sense) and ironicity. Tender love of all new European metaphysicians, especially in the 20th century, is in no case accidental. Inevitability of the end presses every form of existence and therefore makes them processes where there is a necessity of being concluded with something definite, final. Literature, life, creation are limited, exhaustibility and visible convincing finiteness create them, bring them under the idea, of contemporaneity.